The association of plasma sortilin with essential hypertension and subclinical carotid atherosclerosis: A cross-sectional study - Chu, Xinglin; Liu, Rui; Li, Chunli; Gao, Tao; Dong, Yongqi; Jiang, Yi; Ke, Dazhi (Frontiers in Cardiovascular Medicine, 2022)
Background Sortilin, a protein that regulates glucose and lipid metabolism, has recently been linked to cardiovascular diseases (CVDs) such as coronary heart disease and carotid artery stenosis. In this study, we measured circulating sortilin concentrations in essential hypertensive (EH) patients, and evaluated the association between sortilin, hypertension, and subclinical carotid atherosclerosis in hypertensive individuals. Methods This cross-sectional study included 336 individuals, including 186 newly diagnosed EH patients and 150 age-and-sex-matched normotensive healthy subjects (NT). Plasma sortilin and adiponectin (ADI) levels were measured using ELISA kits. In the EH group, high-resolution B-mode ultrasound was used to detect the existence of subclinical carotid atherosclerosis (subAS), which was defined as having a carotid intima–media thickness (cIMT) ≥ 1.0 mm and/or plaque on the carotid artery without any clinical manifestations. Results Our findings showed that plasma sortilin concentrations ranged from 3.34–11.34 ng/ml for all subjects. Sortilin levels were significantly higher in the EH group than in the NT group (8.10 ± 1.82 ng/ml vs. 6.37 ± 1.52 ng/ml, P < 0.001) and were further upregulated in the EH with subclinical carotid atherosclerosis (EH + subAS) group compared to the EH without subclinical carotid atherosclerosis (EH-subAS) group (8.42 ± 1.75 ng/ml vs. 7.79 ± 1.84 ng/ml, P < 0.05). In correlation analysis, sortilin was positively correlated with systolic blood pressure (SBP), diastolic blood pressure (DBP), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), white blood cell (WBC), endothelin-1 (ET-1), high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), and cIMT (all P < 0.05) and negatively associated with NO and ADI (P < 0.001). Multiple linear regression analysis revealed that SBP, LDL-C, and ET-1 were independently associated with plasma sortilin levels. Increased sortilin levels were independently associated with the risk of EH (OR: 1.86, 95%CI: 1.56–2.20, P < 0.001) and EH + subAS (OR: 1.33, 95%CI: 1.07–1.66, P = 0.011), after adjustment for multiple risk factors. Restricted spline curve showed that elevated sortilin levels increase the odds of having EH. Conclusion Elevated sortilin levels are associated with an increased risk of essential hypertension and subclinical carotid atherosclerosis in hypertensive patients.